The Effect of Leadership, Motivation, Work Discipline and Work Environment on Employee Performance at Fast Food Restaurants in Batam - Yuddy Giovanna Priscilla; Widi Waisaka; Dhita Hafizha Asri (Cita Konsultindo Research Center, 2023)
This research is to help determining the impact of leadership, environment of work, motivation and also discipline of work toward performance of employee in several fast food restaurants in Batam. This study is a comparative causal study that has a sample of 5 out of 30 fast food restaurants located in Batam. The results of this research were analyzed descriptively and quantitatively. According to the results, it is stated that the four variables, namely leadership, motivation, work environment and work discipline, each have a significant and positive influence on employee performance. All of the hypotheseses are accepted. The independent variable effected 92.4% toward performance of employee, knowing from the coefficient of determination.